Otolaryngology Workforce Projections in the United States, 2021–2036 - Lorik Berisha; Aman M. Patel; Alan Nguyen; Roshan V. Patel; Sapan M. Patel; Hassaam S. Choudhry; Rohini Bahethi; David W. Wassef; Paul T. Cowan; Ghayoour S. Mir; Andrey Filimonov (Laryngoscope Investigative Otolaryngology, 2025)
ABSTRACT Objective To analyze projections of otolaryngology workforce supply and demand in the U.S. from 2021 to 2036. Methods Otolaryngology workforce projection data from the Bureau of Health Workforce (BHW), Health Resources and Services Administration's (HRSA) Health Workforce Simulation Model (HWSM), and National Center for Health Workforce Analysis (NCHWA) were collected and analyzed to project supply versus demand from 2021 to 2036. The adequacy of the projected otolaryngology workforce, measured as the supply–demand ratio, was the main outcome measurement. Results In 2021, it was assumed that the supply of otolaryngologists matched the demand. From 2021 to 2036, the total otolaryngologist supply is projected to decrease from 11,800 full‐time equivalents (FTEs) to 11,620 FTEs, a 1.5% decline, while total demand is projected to increase by 1050 FTEs (8.9% increase) to 12,850 FTEs. This projects a growing shortfall of 1230 FTEs, resulting in 90.4% workforce adequacy. The projected adequacy is geographically disparate, with 98% workforce adequacy in metropolitan areas versus 35.1% in nonmetropolitan areas by 2036. By this date, otolaryngology is projected to have the third highest rate of workforce adequacy (90.4%) among eight surgical specialties studied. Conclusion Though the HRSA's HWSM predicts a minor shortfall in the otolaryngology workforce supply compared to demand by 2036, the impact on workforce adequacy is significant. Regional variations and scenario outcomes underscore the need for continued research to update these forecasts, which carry important implications for physicians, patients, and policymakers in addressing workforce disparities and ensuring equitable access to otolaryngologic care across the nation. Level of Evidence 4.